Penggunaan Data Google Trends Untuk Mengetahui Minat Publik Tentang Sistem Pemilu Proporsional - M. Yusuf Samad; Taryana Brata; Denggan Parange Sinurat; Andi Yakub; Pratama Dahlian Persadha; Diah Ayu Permatasari (Jurnal Kajian Ilmiah, 2024)
A number of polemics ahead of the 2024 elections have begun to emerge, one of which is a polemic regarding the electoral system used in the upcoming 2024 elections, namely a lawsuit against the Election Law regarding the open proportional system on November 14, 2022. However, the lawsuit did not become a public concern until the first hearing was held on November 23, 2022. The lawsuit became a public concern when it entered the beginning of 2023 until mid-2023. This research aims to find out about what events make the trend of public interest increase and the extent of public exploration related to the proportional electoral system. This research method uses a qualitative approach with a case study research type, the research data is obtained through Google Trends which is then analyzed in accordance with the research objectives. The results show that public interest in proportional electoral systems correlates with events related to these systems, such as political parties' attitudes towards closed and open proportional electoral systems. In addition, public interest trends develop specific searches on closed proportional electoral systems and open proportional electoral systems.